Comparing migration experiences of Venezuelan women and girls: a mixed-method, cross-sectional analysis of refugees/migrants in Ecuador, Peru and Brazil - Bradley P Stoner; Susan A Bartels; Sofia Friesen; Monica Noriega; Belen Rodriquez; Maria Marisol Garcia; Julianna M Deutscher; M Sofia Luna-Siachoque; Sydney Johnson; Maegan Mcconnell (BMJ Publishing Group, 2023)
Objective Over the past decade, geopolitical turmoil in Venezuela has resulted in the displacement of 7.1 million people, resulting in a migration and refugee crisis.Methods and analysis This current cross-sectional, mixed-method research, which is focused on women and girls, examines differences in Venezuelan refugee/migrant demographics, migration characteristics, experiences and perceptions across nine locations in Ecuador, Peru and Brazil.Results A total of 9116 Venezuelan refugees/migrants shared 9339 migration experiences. Respondents in Brazil had been displaced for less time, reported more extreme poverty, perceived that they had received more support from the host community, and had more positive migration experiences. In contrast, respondents in Peru had been displaced for longer, were more likely to share experiences of insecurity/violence, perceived that they had not received adequate support and were more likely to report that the migration experience was negative. Respondents in Ecuador tended to provide more moderate responses somewhere between those from Brazil and Peru with one exception being around the impact of COVID-19, which they perceived more negatively.Conclusion It is critical to recognise that Venezuelan refugee/migrant populations are not homogenous and that their experiences, needs and priorities vary by location of settlement and migration route. From these findings, we recommend more open regularisation policies for Venezuelan nationals in Ecuador and Peru in addition to improved socioeconomic integration in accordance with the Quito Process. Sharing of successful models from other contexts may prove helpful.